Dentoalveolar and maxillofacial surgery - Stanko, Peter, 1954-; Poruban, Dušan, 1953-; Novotňáková, Daniela; Hollý, Dušan; Lekárska fakulta Univerzity Komenského v Bratislave (Bratislava : Comenius University in Bratislava, 2020)
This monograph students used it for learning, the book disappeared from the faculty liberary and a reedition was required. But the authors felt that simple reedition would be not sufficient. Within the time progress has been done in many aspects of the dentoalveolar and maxillofacial surgery. That is why updated information was included along with innovated examination algorithms, surgical protocols and progressive methods of treatment providing contemporary state of the art. Study references were refreshed. Also experience from examinations of our pregraduate and postgraduate students led us to improve some formulations in the text and make them more clear.
Bibliogr. odkazy
Skratky
Keywords: chirurgia ústnej dutiny -- metódy -- vybavenie prístrojové a nástrojové; výkony chirurgické stomatologické a maxilofaciálne -- metódy -- vybavenie prístrojové a nástrojové